Route optimizing and following for autonomous underwater vehicle ladder surveys. (22nd November 2018) - Jiang, Yanqing; Li, Ye; Su, Yumin; Zhou, Ziye; Ma, Teng; An, Li; He, Jiayu
An autonomous underwater vehicle is able to conduct coverage detections, such as sea terrain mapping and submerged objects detection, using sonar. This work addresses the task of both optimizing and following routes that present a ladder shape. First, a planning method to determine a nearly optimal coverage route is designed. The track spacing is optimized considering the seabed type and the sonar range for the purpose of increasing detection probability. It also adds adaptability to confined water, such as harbors, by decomposing the geometrically concave mission region during the processing of the environmental data. Next, a decoupled and two-layered structure is adopted to design the following controller. The route is followed in the form of sequenced-lines tracking. A proportion–integral–derivative algorithm with fuzzy parameters adjustment is employed to calculate a reference heading angle according to the transverse position deviation in designing the guidance controller. An adaptive nonlinear S-surface law is adopted to design the yaw control. The route following the method is demonstrated with sonar (including side scanning sonar and multi-beam echo sounder) imagery collected in terrain mapping and object detection through sea trials.